Analysis of The Relationship of Shipment Time and Productivity of Drilling Equipment and Transportation, Java Province - Eko Purnomo; Yazid Fanani; Avellyn Shinthya Sari (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
PT. Agung Satriya Abadi is engaged in mining sand and stone which is formed by weathering deposits, located in Wonosunyo village, Gempol District, Pasuruan Regency, East Java. Companies that run in this category of rock mining generally have quite complex problems, one of which is in terms of time management which is considered less attention by some rock mining companies. In this study, several analyzes will be carried out and run the scientific method.The analysis carried out in this study uses statistical methods by displaying mathematical modeling and analysis of the relationship between circulation time and productivity in linear regression analysis. The data values that arise from the use of this mathematical-statistical method are the value (R2) = 0.8597 or 85% of the Doosan Giant Dx 520 Lca, then the value (R2) = 0.8459 or 84% of the Doosan Giant 300 Class, then Hino Ranger 500 Fm 260 Ti paired with Doosan Giant Dx 520 Lca has a value of (R2) = 0.9868 or 98%. And lastly, the Hino Ranger 500 Fm 260 Ti paired with the Doosan Giant 300 Class has a value of (R2) = 0.9886 or 98%.The data generated from each distribution time and productivity relationship from Doosan Giant Dx 520 Lca generates a difference value = 13,031 m3/hour, Doosan Giant 300 Class gives a difference value = 31.347 m3/hour, Hino Ranger 500 Fm 260 Ti against Doosan Giant Dx 520 Lca raises the difference value = 1,659 m3/hour, Hino Ranger 500 Fm 260 Ti against Doosan Giant 300 Class raises the difference value = 1,492 m3/hour.